Identification of Small-Molecule Inhibitors for Osteosarcoma Targeted Therapy: Synchronizing In Silico, In Vitro, and In Vivo Analyses - Liu, Juan; Yao, Qi; Peng, Yu; Dong, Zhihong; Tang, Lu; Su, Xiaoyu; Liu, Lishuang; Chen, Cheng; Ramalingam, Murugan; Cheng, Lijia (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: To explore a new approach for the treatment of osteosarcoma through combining biomaterials with next-generation small molecule-based targeted therapy. Methods: The model of osteosarcoma was established by 4-hydroxyaminoquinoline 1-oxide (4-HAQO) in mice, while the collagen-thermosensitive hydrogel-calcium phosphate (CTC) composite biomaterials were prepared, and the small molecule inhibitors were virtually screened and synthesized. Then the MG-63 cells were used to validate our bioinformatics findings in vitro, and the osteosarcoma models were treated by combing CTC composites and small molecule inhibitors after debridement. Results: Five compounds, namely ZINC150338698, ZINC14768621, ZINC4217203, ZINC169291448 and ZINC85537017 were found in the ZINK database. Finally, ZINC150338698 was selected for chemical synthesis and experimental verification. The results of MTT assay and Hoechst staining showed that the small molecule inhibitor ZINC150338698 could significantly induce osteosarcoma MG-63 cell death. Furthermore, CTC composites could repair the bone defects well after debridement of osteosarcoma, and the ZINC150338698 further inhibited the recurrence and metastasis of osteosarcoma. In addition to that, the biomaterials and small molecule inhibitors have good biocompatibility and biosafety. Conclusion: Our findings not only offer systems biology approaches-based drug target identification, but also provide the new clues for developing novel treatment method for future osteosarcoma research.